The influence of revenue sources on the financial independence and investment activity of communes and cities with ‘powiat’ rights in Poland - Surówka, Krzysztof (Wpływ źródeł dochodów na samodzielność finansową i działalność inwestycyjną gmin i miast na prawach powiatu w Polsce, 2019)
Local government is a part of the public finance sector, therefore a significant part of its income has a strictly defined purpose. Such focusing of income on the financing of specific tasks limits the scope of the financial autonomy of local government and reduces it to the role of administering public funds and spending them on financing particular tasks. Supervision and control over local government are also a limitation of financial independence of local government units (LGUs) − municipalities, districts and voivodeships. At the same time, however, the essence of local government lies in the fact that it is focused on local development. Owing to this, local authorities have their own income at their disposal and can also access extraordinary sources of financial power, such as loans and credits. This duality government functioning can be the cause of its numerous real and financial problems, especially when the repartition of public funds between the central authority and local government is made incorrectly. The article focuses on the problems related to the issues of the influence of revenue sources on the financial independence and investment activity of municipalities in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 136-154
Keywords: local government units; LGUs; finacial independence; revenue sources; operating surplus; investment activity; Poland; jednostki samorządu terytorialnego; JST; samodzielność finansowa; źródła dochodów; nadwyżka operacyjna; działalność inwestycyjna; Polska